2012
DOI: 10.1097/brs.0b013e3182666adc
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Radiation (Fluoroscopy) While Maintaining Safe Placement of Pedicle Screws During Lumbar Spine Fusion

Abstract: Objective: The purpose of this study is to report the results using PediGuard (electrical conductivity device) to reduce radiation exposure while drilling the pilot hole for pedicle screw placement. Method: Eighteen patients diagnosed with a degenerative lumbar spine, that required a posterior spinal fusion. Average age of the patients were 55 ± 12 years. Patients received postoperative CT scans of all screws. Scans were reviewed by an independent reviewer grading 'in' < 2 mm of breach , or 'out' > 2 mm of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…Bolger et al [26] reported on 28 spinal operations with this particular device and noted a 16 % rate of pedicle perforations which were nearly all (96 %) detected by the system. A more recent study [27] showed no difference in screw accuracy with or without the PediGuard but found that fluoroscopy usage could be decreased significantly. The authors nevertheless admit that the PediGuard can give rise to false positives for breach in particular when the surgeon relaxes pressure from the probe and allows blood to reach the tip of the instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolger et al [26] reported on 28 spinal operations with this particular device and noted a 16 % rate of pedicle perforations which were nearly all (96 %) detected by the system. A more recent study [27] showed no difference in screw accuracy with or without the PediGuard but found that fluoroscopy usage could be decreased significantly. The authors nevertheless admit that the PediGuard can give rise to false positives for breach in particular when the surgeon relaxes pressure from the probe and allows blood to reach the tip of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally 24 % (16 screws) of thoracic and 15 % (21 screws) of lumbar screws caused cortical breach in either horizontal, vertical or both directions, but had stimulation thresholds above 10 mA (false negatives, Table 2). Split into three regions (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and [30 mA, Fig. 2) the stimulation threshold range of 10-20 mA hosts both, the majority of correctly placed and the majority (67 %) of misplaced thoracic screws.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, once a nerve root injury has taken place, changing the direction of the screw does not alter the outcome.'' 1 Other pressure-and electrical conduction-based techniques to verify pedicle accuracy, such as specialized piezoelectric piercer probes, can also lead to misplaced pedicle screws 31 and can result in false-negative errors. 32,33 Other emerging techniques such as intraosseous ultrasound, [34][35][36][37][38][39] robotic guidance, or near-infrared spectroscopy, require substantial equipment and are not without false-negative errors.…”
Section: Discussionmentioning
confidence: 99%
“…1A–1D) and a multi-axis angiography unit. 3,4) ECD was designed as a free hand drilling instrument that measures electrical conductivity. 5) Electrical conductivity is measured at the tip of the probe, allowing relative differentiation of tissue conductivity, which is measured at five samples per second, and then the information is converted to sound in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ECD emits a high frequency and pitch as a warning sound when the probe makes contact with soft tissue or a blood component slightly outside of the cortical bone. 3,4) Bolger et al 5) reported that the detection rate of pedicle breaches during the actual pedicle drilling with ECD is superior to only sensation by surgeon.…”
Section: Introductionmentioning
confidence: 99%